Analisis Hukum Adat terhadap Pergantian Tu'a Golo di Gendang Warat, Kabupaten Manggarai Timur - Amelia Aquinas; Juliana S. Ndolu; Petornius Damat (Universitas Palangka Raya, 2026)
The succession of the Tu'a Golo constitutes an essential component of the indigenous leadership system of the Manggarai community, which is regulated by customary law and preserved through generations. In 2024, the succession process in Gendang Warat generated controversy because the transfer of leadership from the eldest lineage to a younger sibling's lineage was perceived as inconsistent with established customary norms. This study aims to analyze the requirements and succession process of the Tu'a Golo and to examine its implications for the indigenous community of Gendang Warat. This research employed an empirical legal method with a descriptive qualitative approach. Primary data were collected through interviews with the Tu'a Golo, customary leaders, community leaders, and indigenous community members, while secondary data were obtained through a literature review. The findings reveal that the succession of the Tu'a Golo is primarily based on patrilineal genealogy, customary knowledge, moral integrity, leadership capacity, and collective recognition through customary deliberation (Lonto Leok). However, the 2024 succession did not fully comply with customary provisions, resulting in differing interpretations, weakened leadership legitimacy, declining public trust in customary institutions, and social tensions within the community. Strengthening adherence to customary procedures and participatory deliberation is therefore essential to preserve leadership legitimacy, social harmony, and the continuity of Manggarai customary law.